The Role of Ethical Belief, Accounting Literacy, and Digital Literacy in Village Financial Management - Arif, Ahmil Fauzan; sahrir; Andika Rusli (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2026)
This study is motivated by the need to strengthen accountable and transparent village financial management. The objective of this research is to examine whether ethical beliefs, accounting literacy, and digital literacy influence village financial management among village officials in North Luwu Regency. A quantitative associative approach was applied. The study involved 120 village officials directly involved in financial management, selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that ethical beliefs and digital literacy significantly affect village financial management, while accounting literacy does not show a significant partial effect. However, simultaneously, the three variables have a significant influence. These findings imply that ethical integrity and digital competence among village officials play a crucial role in improving the quality of village financial management practices.